Reckoning with the wicked problems of nuclear technology: pedagogical philosophy, design, and method underlying a course on nuclear technology, policy, and society - Verma, Aditi (Frontiers in Nuclear Engineering, 2024)
Many problems at the intersection of nuclear technology, policy, and society can be thought of as wicked problems. Wicked problems — a formulation put forward in what is now a landmark paper by Rittel and Webber (design and planning scholars respectively) – are those that lack definitive formulations, resist durable resolution, do not have an exhaustively identifiable set of true or false solutions, and are often framed entirely differently by different entities experiencing the problem. Every attempt to solve a wicked problem is a solution attempt made in the real world and thus has consequences and implications that can potentially be far-reaching. This paper describes the underlying philosophy, design, and implementation of a course on “Nuclear Technology, Policy, and Society” taught in the Department of Nuclear Engineering and Radiological Sciences at the University of Michigan. The course explores some of nuclear technology’s most pressing challenges (or its ‘wicked problems’). Through this course students explore the origins of these problems – be they social or technical, they are offered tools – conceptual and methodological – to make sense of these problems, and guided through a semester-long exploration of how engineers can work towards their resolution, and to what degree these problems can be solved through institutional transformation and/or a transformation in our own practices and norms as a field. The underlying pedagogical philosophy, implementation, and response to the course are described here for other instructors who might wish to create a similar course, or for non-academic nuclear engineers, who might perhaps, in these pages, find a vocabulary for articulating and reflecting on the nature of these problems as encountered in their praxis.